A functional programming approach to hypermedia authoring - Marcos, Daniel H.; Martínez López, Pablo Ernesto; Risi, Walter A. (1998)
Avoiding boxing when representing native objects is essential for the efficient compilation of any programming language For polymorphic languages this task is difficult, but several schemes have been proposed that remove boxing on the basis of type information. ...
Formato de archivo: PDF. -- Este documento es producción intelectual de la Facultad de Informática - UNLP (Colección BIPA/Biblioteca)
ACM SIGPLAN international conference on Functional programming (3º : 1998 : Baltimore). Proceeding. Nueva York, ACM SIGPLAN notices,1999(1), pp. 346.
Keywords: HIPERMEDIA; APLICACIONES HIPERMEDIA